STUDY OF THE SEDIMENTATION TREND IN THE PROSPECTIVE AREA OF PORT OF MARINE CENTER, CIREBON BASED ON REMOTE SENSING DATA - Undang Hernawan (BULLETIN OF THE MARINE GEOLOGY, 2009)
A coastal zone is the interface between the land and water that influenced by both of them. Coastal dynamic is influenced by many factors from land and sea, such as sedimentation and current. In order to support marine facility, Marine Geological Institute of Indonesia (MGI) plan to build a port. The prospective area is behind MGI office at Cirebon. This study use multi temporal remote sensing data in order to observe trend of coastline change around MGI. Based on the interpretation of the data, there are sedimentation around the MGI water and abrasion due to the presence of Kejawananâ€™s jetty and Kalijaga River. The result also shows that the current in this region is moving from southeast to northwest. The presence of the Kejawananâ€™s jetty stymies the movement of sediment. The sediment which is normally moving to the north of the jetty is then trapped on the south side of the structure, so that the sediment precipitates in this region and makes it as the active region of sedimentation and accretion. The presence mangrove conduces to support sedimentation speed and accretion at this region, because of his function as the catchment area. Abrasion occurs in the eastern part of MGI office at the Kalijaga river mouth within the bay. The Kalijaga River mouth is predicted to be the primary source of sedimentation in this area. The coastline change caused by sedimentation will be continuing as long as it is supplied by the sediment. The direction of the sedimentation is parallel to the jetty and it forms ellipsoid, with the sedimentation/accretion region is behind MGI office. The abrasion area is found in Kalijaga River mouth and a small area beside Kalijaga River. In order to build a port, we have to consider this sedimentation process. One of the alternatives to build the port is to make a quay pile model which gives way the current to pass through the other side of the port. Another alternative is to build the port as a pond model but it needs accuracy in building the mouth of jetty to minimize the sedimentation process. Keyword : sedimentation, Cirebon, remote sensing Pantai/pesisir merupakan wilayah antara daratan dan lautan yang masih dipengaruhi oleh keduanya. Dinamika pantai dipengaruhi oleh faktor-faktor dari daratan dan lautan seperti sedimentasi dan arus. Untuk menunjang â€œmarine facility centerâ€ Puslitbang Geologi Kelautan (P3GL) bermaksud untuk membangun pelabuhan. Daerah yang prospektif adalah di belakang kantor P3GL, Cirebon. Studi ini menggunakan data citra satelit multi temporal, yang berguna untuk melihat arah perkembangan dan perubahan garis pantai di belakang kantor P3GL dan sekitarnya. Berdasarkan interpretasi data citra, di daerah studi ditemukan adanya daerah akresi/sedimentasi dan daerah abrasi yang disebabkan oleh adanya dermaga Kejawanan dan adanya sungai Kalijaga. Hasil studi juga menunjukkan arah arus umumnya bergerak dari tenggara menuju barat laut. Keberadaan jetty Kejawanan menyebabkan aliran arus dan sedimen terhenti. Sedimen yang seharusnya bergerak ke arah utama menjadi terhalang dan terjebak di bagian selatan jetty, sehingga mengendap di daerah ini. Keadaan ini menyebabkan daerah ini menjadi daerah sedimentasi yang aktif (akresi). Keberadaan mangrove pada daerah ini juga menambah kecepatan sedimentasi di daerah ini, karena berfungsi sebagai daerah tangkapan sedimen. Abrasi terjadi di sebelah timur P3GL, tepatnya pada daerah lengkungan teluk dan di mulut sungai Kalijaga. Daerah mulut sungai Kalijaga diprediksi sebagai sumber sedimen pada daerah ini. Perubahan garis pantai yang disebabkan oleh sedimentasi akan terus berlangsung di daerah ini, selama adanya pasokan sedimen. Sedimentasi ini akan berlangsung sampai arahnya sejajar dengan jetty Kejawanan dan akan membentuk ellipsoid, dengan daerah sedimentasi berada di sekitar jetty dan belakang P3GL sementara daerah abrasi berada di sungai Kalijaga dan daerah sebelahnya. Karena itu, pembangunan pelabuhan P3GL sebaiknya memperhatikan kondisi ini. Salah satu alternatifnya adalah dengan membuat pelabuhan model tiang pancang yang memungkinkan arus dan sedimen untuk bergerak ke sisi sebelahnya. Alternatif lain adalah dalam bentuk kolam pelabuhan, tetapi harus tepat memperhatikan mulut pelabuhan untuk meminimalkan sedimentasi yang terjadi.